Effect of plant density and drastic prunning on tomato yield inside a plastic greenhouse - Streck, Nereu Augusto; Buriol, Galileo Adeli; Andriolo, Jerônimo Luiz; Sandri, Miguel Angelo (Pesquisa Agropecuaria Brasileira, 1998)
Yield response of "Monte Carlo" tomato (Lycopersicon esculentum), to high plant densities and prunning systems inside a plastic greenhouse was evaluated at Santa Maria, RS State, Brazil. Treatments were: 20,000, 40,000, 80,000 and 100,000 plants ha-1 prunned at 2nd or 3rd cluster and 30,000 and 40,000 plants ha-1 prunned at 7th cluster. Tomato plants were conducted by one steam. The experiment was carried out during winter-spring crop-season. Marketable fruit yield was higher when plants were grown at 80,000 and 100,000 plants ha-1 densities with three clusters. These yields were similar to the treatments with seven clusters. It was observed a significant reduction in fruit harvest period in the treatments with drastic prunning without substantially reduce yield.